Comparative efficacy of programmed death ligand 1 inhibition and chemotherapy in advanced gastric or gastroesophageal junction cancer with combined positive score – a meta-analysis - Shaibu, Zakari; Yang, Fumeng; Ting, Liu; Dzidula, Lily; Yusuf, Amina Elmi; Chen, Zhi-hong; Zhu, Wei (Contemporary Oncology/Współczesna Onkologia, 2024)
Advanced gastric and gastroesophageal junction cancer (G/GEJC) poses significant therapeutic challenges. Immune checkpoint inhibitors, particularly targeting programmed cell death ligand-1 (PD-L1), have emerged as promising agents to enhance patient outcomes. This meta-analysis evaluates the efficacy of PD-L1 inhibitors compared to chemotherapy in patients with advanced G/GEJC characterised by varying combined positive scores (CPS). We systematically searched PubMed, Google Scholar, and Web of science for clinical trial studies comparing PD-L1 inhibitors and chemotherapy in CPS-positive patients, focusing on studies published up to 10 April 2023. Studies were evaluated with risk of bias tools. The primary clinical endpoint analysed in this study was overall survival (OS), and the secondary endpoint was progression-free survival (PFS). This study is registered with Prospero (CRD42023495607). A total of 10 studies comprising 4522 participants were included. Our analysis revealed no statistically significant difference in CPS values between PD-L1 inhibitors and chemotherapy groups (≥ 1 : 1.03 [95% CI: 0.86–1.24], ≤ 1 : 0.92 [95% CI: 0.77–1.11]). However, the pooled hazard ratio for OS favoured PD-L1 inhibitors (hazard ratios – HR, 0.83, [95% CI: 0.78–0.88] and p < 0.00001), while PFS was better after chemotherapy (HR 1.28, [95% CI: 1.04–1.58], p = 0.02). Program death ligand-1 inhibitors improve OS, while chemotherapy enhances PFS in advanced G/GEJC, warranting further investigation into the impact of CPS on treatment outcomes.